Propolis: A New Alternative for Root Canal Disinfection - Jahromi, Maryam Zare; Toubayani, Hasan; Rezaei, Majid (Iranian Endodontic Journal, 2012)
Introduction: This study evaluated and compared colony forming units (CFUs) and minimum inhibitory concentrations (MICs) of calcium hydroxide and propolis as intracanal medicaments. Materials and Methods: Eighty human single-root and caries-free teeth were selected and divided into five groups. Crowns were removed. Root canals were then prepared in a step-back manner. The samples were then inoculated by Enterococcus (E.) faecalis and incubated for 21 days. Intracanal medications were applied including, calcium hydroxide (n=20), propolis (n=20), and ethanol (n=20). Two groups of 10 teeth were also used as the positive and negative controls. Microbiological sampling was performed utilizing a piezo-reamer drill after one week of incubation. The samples were plated and CFUs were counted after 48 hours. MICs of calcium hydroxide and propolis were measured by serial dilution and agar dilution methods, respectively. The statistical tests of ANOVA and Duncan post-hoc were used to compare different medications. Results: MICs and CFUs of propolis were dramatically less than calcium hydroxide. The difference between the groups was statistically significant (P<0.001). Conclusion: Our results reveal that propolis is an effective antimicrobial intracanal agent.